Lubricated wear behaviour of SiC reinforcement on TI-6AL-4V alloy based on Taguchi approach - Maleque, Md. Abdul; Lailatul, H.; Bello, K.A.; Azwan, M. (2016)
Titanium alloy grade 5 (Ti-6Al-4V) is widely used in engineering industries as compared to the other titanium alloys. Ti-6Al-4V also has been known to show good mechanical properties, excellent corrosion resistance and having low density [1]. However, the grade 5 titanium alloys have poor tribological properties since it has poor wear resistance, low degree of hardness and high coefficient of friction [2]. There is a need to improve these properties to increase the performance of the engineering components and to extend their life service without any failure. Previous research work by Adeleke & Maleque [3] studied the surface alloying of commercial purity titanium (CP-Ti) using preplaced Fe-C-Si powder by TIG techniques. The surface modified CP-Ti alloy exhibited hardness values ranging from 600 Hv to 800 Hv which was 3 to 3.5 times higher than base metal hardness. The higher hardness observed at particular areas are attributed to high population and big sizes of dendritic microstructures of TiC. The main aim of this study is to improve the tribological properties of grade 5 (Ti-6Al-4V) under lubricated condition based on Taguchi approach. The substrate alloy was preplaced with silicon carbide (SiC) powder and tungsten inert gas (TIG) torch surface melting technique was applied.